Spectrum of breast cancer patients: twin institutional study - Nichkaode, Prabhat B.; Parakh, Aditya (International Surgery Journal, 2017)
Background: Breast cancer is emerging as one of the most common cancer occurring in urban female population of India. It has become the second most common cancer in rural India, after cancer of uterine cervix. One must understand the diversity of presentation of breast cancer patients in the rural and urban population. Author is a surgeon working in a hospital which caters health care to both, rural as well as urban population. The present study is meant to review the data of various types of presentation, of cancer breast in two Institutes in different states. We also would like to compare our data with a few major cancer centers in metropolitan cities. The aim of the study was to present a data of patients with breast cancer at two institutes. Methods: This is a retrospective observational study carried out at two different medical teaching Institutes, CCM Medical College, Kachandur, Durg, Chhattisgarh and other at NKP Salve Institute of Medical Sciences Nagpur, Maharashtra. Study was carried out from 2009 till 2016 and total of 167 patients were included in the study. Data like age, menstrual status, size of lump, stage of disease, grade of disease (Bloom Richardson Elliston Index) and ER, PR, HER/neu receptor status of tumor, presence or absence of metastasis, and follow up records related to outcome, are presented in this study. Results: Out of 167 patients included in the study, two patients were males, and were excluded from our study. It becomes a study of 165 patients. Average age of patients at presentation was between 35 to 65 years. Majority of patients belong to stage III a (bulky operable disease) or III b, (locally advanced breast cancer) Stage II, and stage IV -metastatic disease. No patient of stage I disease reported in the present study. Most common pathological type was infiltrating ductal carcinoma. Conclusions: Breast cancer has emerged as the commonest cancer in urban India, with second most common cancer in rural India. Majority of our patients present with advanced disease stage with numerous poor prognostic factors such as young age, larger tumor size, lymph node metastasis, high pathological grade and poor hormone receptor status. These factors are a reflection of poor health awareness for breast cancer, general indifference towards women’s health, poor financial resources, unavailability of multimodality treatment facilities.